Goričan Mihael Rabatta, avtor potopisa Iter sancti sepulcri. - Pavlin, Vojko (Clotho, 2024)
Michele Rabatta went to the Holy Sepulchre with his friend Morando Porcia in 1396 and left a chronicle of their journey, which is preserved in the State Archives in Gorizia (Archivio di Stato di Gorizia). The transcription of his travelogue Iter sancti sepulcri was published in 2007 in Pordenone by the Accademia San Marco. The travel diary describes a journey that lasted three months, from 27 August to 28 November 1396. Drawings and sketches of some of the places have been preserved. The text draws particular attention to the indulgences that were awarded to pilgrims visiting Jerusalem and other biblical sites. Michele Rabatta served the Carrara lords of Padua as a soldier and diplomat from the early 1370s, remaining loyal to them until the fall of Padua to the Venetian Republic in 1405. He was known in diplomatic circles not only in the northern Italian area but also, and above all, at the royal court of Hungary. His diplomatic skills were in demand both by the Patriarchs of Aquileia in Friuli and by the Counts of Gorizia. Michele's father, Antonio, came to Gorizia from Tuscany. The family got its name after the village of Rabatta near Borgo San Lorenzo. The late medieval trilingual Gorizian environment in which Michele grew up gave him knowledge also of Slovene and German. Shortly after he arrived from the Holy Land, Michele received Dornberk Castle as a fief from the Counts of Gorizia. Dornberk Castle thus became the core of the Rabatta family's estate in the county of Gorizia until the family's extinction in 1794. In March 1398, Michele and his brother Giovanni, who was the governor of Henry IV, Count of Gorizia, obtained Pope Boniface IX's permission to build the Church of the Holy Spirit below Gorizia Castle. A third brother, Pietro, the parish priest of Solkan-Gorizia, was also indirectly involved. The Rabattas were therefore a prestigious family in Gorizia in their time.